Physics and Technology of Nanostructured Materials, IV - Galkin, Nikolay Gennadievich (Solid State Phenomena ;, 2016)
Collection of actual researches and decisions in area of semiconductor, magnetic, ferroelectric nanostructures and functional hybrid materials. This publication will be useful for a wide range of researchers and engineers in the field of nanostructured materials for modern and future industry.